Neighborhood Correlates of Sitting Time for Australian Adults in New Suburbs: Results From RESIDE - Foster, S.; Pereira, Gavin; Christian, H.; Knuiman, M.; Bull, F.; Giles-Corti, B. (Sage Publications, Inc., 2015)
The neighborhood influences on walking are well recognized, yet less is known about how the environment impacts sedentary behaviors. This study used a social-ecological model to examine the correlates of sitting time, independent of walking behavior. Objective built environment measures and self-reported community participation were examined for associations with sitting time for 1,179 residents in Perth, Western Australia. Neighborhood built environment and social factors were significantly associated with women’s sitting time only. In particular, the presence of community infrastructure was negatively associated with women’s weekday sitting (relative reduction = 0.951; p = .037), but statistical significance weakened after accounting for community participation (relative reduction = 0.951; p = .057). Community participation was independently associated with both women’s weekday and weekend sitting (both p < .001). More walkable neighborhoods may help limit women’s sitting time by providing better access to community infrastructure, as local venues may afford additional opportunities for social interaction and participation.